Pengaruh Kadar Raksa Dalam Rambut Terhadap Keparahan Gejala Autisme pada Anak yang Mengalami Gangguan Autistik - Ellyta Aizar; Yahwardiah Siregar; Zul Alfian (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. Autistic Disorder can happen due to neurological expressions as the effects of environmental poisons in children who had genetical deficiency history. Current study found that increasing of mercury (Hg) concentration in hairs had significant correlation towards increasing of autisme level of severity. Hair analysis may identify the history of mercury’s exposure in human. This analytical correlational descriptive study aimed to identify mercury (Hg) concentration in children with autistic disorder at YAKARI Autism Foundation in Medan and at State Disability School in Binjai. This study also aimed to analyze the correlation between the Hg concentration and the symptoms’ level of severity. Hair samples were taken from 17 children with autistic disorder and 17 normal children (at similar age and sex). Mercury concentrations were analyzed by using ICP-OES. CARS were used to examine the autism symptoms’ level of severity. Majority of autistic disorder subjects (70.6%) had severe autism symptoms. Mean of Hg concentrations in autism subjects was 1,82 ppm ± 0,52 and in normal subjects was 0,91 ppm ± 0,68. Furthermore, mean of Hg concentrations in autistic disorder subjects was significantly higher than in normal subjects (p < 0,05). However, there was no significant difference on Hg concentrations between mild-fair and fair-severe autistic subjects’ categories. The findings of this study explain that the severity of autism symptoms in the autistic disorder subjects do not influenced by Hg concentrations within their body. Therefore, unidentified factors in this study might be contribute to the severity of autism symptoms. Future studies related epigenetics need to be conducted in order to explore another factors contribute to the severity of autism symptoms. Keywords: autistic disorder, CARS, mercury (Hg), hair analysis